The Making of a “Correct” Translation Showcasing the Official Chinese Discourse of Translation - Zhong, Yong (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This paper studies political translation in contemporary China. It approaches the issue by tackling a case study of the translations of a maxim issued in 2006 by the Chinese supreme leader, Hu Jintao 胡锦涛. Like many past maxims, this one has been translated many times into English and four of the renditions are sampled for the case study, including seemingly “correct” and “flawed” ones. By comparing the different renditions, the study has managed to address a number of questions, including what makes a “correct” translation, how a “correct” translation is made, what strategies are used to accomplish “correctness” and what the criteria are for the making of a “correct” translation in China. The author hopes that this paper will contribute to an enhanced knowledge with regard to the dominant Chinese discourse of translation and about how translation is organized, regulated and evaluated in China.